RESPON PERTUMBUHAN BIBIT NYAMPLUNG (Calophyllum inophyllum Linn) TERHADAP MEDIA TANAM DAN SUNGKUP PLASTIK - Gita Putri Alkautsar; Sulaiman Bakri; Basir Basir (Jurnal Sylva Scienteae, 2020)
The aims of this study to determine the response of the growth of Nyamplung seedlings to the provision of planting media (soil, sand, and a mixture of both), and maintenance in plastic hoods. The benefit of this research is to provide information on the response of nyamplung seedling growth with various growing media and maintenance in plastic hoods to the growth of nyamplung seedlings which are useful in developing silvicultural techniques for the purpose of nyamplung cultivation to accelerate growth. Analysis data using design random complete (RAL) factorial) with the observation parameter is the increase in height of nyamplung seedlings. The results showed that the maintenance in plastic hoods had a very significant effect on the increase in height with the treatment of planting media in the form of sand, soil and a mixture of both.Keywords: Nyamplung; Media; Plastic hoods; Growth